Protective effect of atorvastatin on oxidative stress in streptozotocin-induced diabetic rats independently their lipid-lowering effects - Aktay, Goeknur; Gursoy, Sule Oner; Uyumlu, Umut; Unuvar, Songuel; Ilhan, Nevin (Wiley, 2019)
In the present study, we investigate the effects of atorvastatin on the lipid profile, oxidative stress, and liver enzyme markers, and its protective activity against diabetic complications, in streptozotocin (STZ)-induced diabetic rats. Fasting blood glucose (FBG), triglyceride (TG), total cholesterol (TC), and high-density lipoprotein (HDL) levels, as well as alanine aminotransferase (ALT) and aspartate aminotransferase (AST) enzyme activities, were measured 7 weeks after the administration of STZ and atorvastatin. Thiobarbituric acid reactive substances (TBARS), non-protein associated sulfhydryl (NP-SH), total sulfhydryl (T-SH), and nitric oxide (NO) levels were measured to evaluate oxidative stress. Atorvastatin was found to inhibit ALT and AST activities and to reduce FBG levels in rats with STZ-induced diabetes. Moreover, atorvastatin treatment significantly reduced lipid peroxidation in kidney, heart, and eye tissues (P < 0.001, for all), and resulted in a significant increase in NP-SH levels in brain tissues (P < 0.001). Total NO and nitrate levels increased significantly after atorvastatin treatment (P < 0.01). Our results revealed that atorvastatin has a protective effect against STZ-induced oxidative damage by reducing TBARS levels and increasing NP-SH levels, has a hepatoprotective effect by decreasing ALT and AST activities. It also shows the antihyperglycemic activity by lowering FBG levels.
Keywords: atorvastatin; diabetes mellitus; lipid peroxidation; liver enzymes; streptozotocin (STZ)